PROSES PEMBUATAN SHAFT M36 MENGGUNAKAN MESIN BUBUT DI PT. PADINA BARAYA JAYA - Damara, Dali; Budiman, Haris (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Shafts M36 made at PT. Padina Baraya Jaya is applied as a binder to the components in the backhoe hand construction equipment. Shafts M36 have a size of 36 482 mm in length, including (Æ25 x 100 mm), (Æ36 x 370 mm), and (Æ25 x 12 mm), in section Æ36 they are threaded with 4 mm screw depth. Shaft M36 is a threaded shaft that serves to bind one engine element to another to get a strong and easy machine construction in its installation and disassembly. The material used in makin Shaft M36 is SS41 steel material, with chemical composition namely (C) 0.14 - 0.22%, (Mn) 0.30 - 0.80%, (Si) ≤ 0.30, and with hardness 68 Hv. Machines used in making shafts M36 are C6132A lathe, 1000 mm working capacity, 350 mm swing. While the tools used are, the caliper, HSS lathe tool, chuck key, tool key / tool post, drill center. The process used is cutting material, face lathe, drill center lathe, standard lathe, and M36 screw lathe. The results of making shafts M36 are obtained by different sizes with working drawings, but still in the size of tolerance -0,1 and -0,2.